Interactions of Bacillus thuringiensis bioinsecticides and the predatory stink bug Podisus nigrispinus to control Plutella xylostella - Magalhaes, G. O. [UNESP]; Vacari, A. M. [UNESP]; Laurentis, V. L. [UNESP]; Bortoli, Sergio Antonio de [UNESP]; Polanczyk, Ricardo Antonio [UNESP] (Wiley-Blackwell, 2015)
The diamondback moth (DBM), Plutella xylostella (L.), is a major pest of brassica crops worldwide. Control of this pest is difficult because it rapidly develops resistance to synthetic and biological insecticides and because of the effects of insecticides on its natural enemies. Podisus nigrispinus (Dallas) is a predator that feeds on its prey, as well as on the host plants of its prey, and is an important biological control agent of DBMs. The aim of this study was to determine the susceptibility of P.xylostella larvae to two bioinsecticides: the HD1 strain of Bacillus thuringiensis (B.thuringiensis var. kurstaki) and the commercial product Agree((R)) (B.thuringiensis var. aizawai CG 91). In addition, the impact of these bioinsecticides on the P.nigrispinus consumption of DBM larvae and phytophagy was evaluated. Both the HD1 strain and Agree((R)) caused 100% mortality in P.xylostella larvae. P.nigrispinus nymphs fed only with kale leaves (Brassica oleracea var. acephala) sprayed with water, the HD1 strain, or Agree((R)) did not complete their nymphal development. When prey was also available, P.nigiripinus fed on kale leaves to obtain water. Both nymphs and adults of P.nigrispinus consumed greater numbers of DBM larvae, and fed less on kale leaves, when sprayed with the HD1 strain or Agree((R)). These results suggest a positive interaction of B.thuringiensis-based products and the predator P.nigrispinus in the control of P.xylostella larvae.
Keywords: Asopinae; Biological control; Diamondback moth; Insect biology; Microbial control